2017
DOI: 10.26858/jds.v5i1.3035
|View full text |Cite
|
Sign up to set email alerts
|

Development Test System Based on Linear Equations Two Variable Revised Taxonomy Bloom to Measure High Order Thinking Skills at Student Class Viii SMPN Sungguminasa Gowa

Abstract: High-level thinking skills based on a revised Bloom's taxonomy is an ability that involves the analysis, evaluation, and create the dikombainkan with dimensions of factual knowledge, conceptual and procedural. This research is the development (Research and Development), which aims to generate test Systems of Linear Equations Two Variables based on a revised taxonomy Bloom qualified to measure high-level thinking skills class VIII SMPN Sungguminasa Gowa. The subjects were the students of class VIII SMPN 4 Sungg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
3
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 1 publication
1
3
0
1
Order By: Relevance
“…In line with these findings, Wahyuni (2017) revealed that the development of Anderson and Krathwolh's Taxonomy on thinking skills could be used to determine the extent of students' thinking skills in solving problems. Meanwhile, Pancaningrum (2016;Filtri & Sembiring, 2018) suggested that the categories of knowledge, analysis, synthesis, and evaluation domains were very well provided with certain learning strategies.…”
Section: Resultssupporting
confidence: 53%
“…In line with these findings, Wahyuni (2017) revealed that the development of Anderson and Krathwolh's Taxonomy on thinking skills could be used to determine the extent of students' thinking skills in solving problems. Meanwhile, Pancaningrum (2016;Filtri & Sembiring, 2018) suggested that the categories of knowledge, analysis, synthesis, and evaluation domains were very well provided with certain learning strategies.…”
Section: Resultssupporting
confidence: 53%
“…Mathematical problem solving is one of the most important things in 4C. According to Hamzah (Wahyuni, 2017), To solve a mathematical problem, students need a higher-order thinking concept, namely the ability to think from the aspect of analyzing to creating. As for critical thinking, Duron et al (2006) state that "critical thinking is very simply stated, the ability to analyze and evaluate information".…”
Section: Introductionmentioning
confidence: 99%
“…HOT merupakan suatu proses berpikir secara kompleks dalam memanipulasi data yang didapatkan sebagai pemahaman baru yang teruji kebenarannya (Wahyuni, 2017). HOT merupakan suatu proses berpikir yang dilakukan dengan menghubungkan, memanipulasi, dan mentransformasi informasi secara kritis dan kreatif untuk memecahkan suatu permasalahan (Rofiah, Aminah, dan Ekawati, 2013).…”
Section: Pendahuluanunclassified